2021
DOI: 10.3389/fcvm.2021.659364
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Concomitant Impairments of the Left and Right Ventricular Myocardial Strain on the Prognoses of Patients With ST-Elevation Myocardial Infarction

Abstract: Background: The impact of concomitant impairments of left and right ventricular (LV and RV) strain on the long-term prognosis of acute ST-elevation myocardial infarction (STEMI) is not clear.Methods: We analyzed CMR images and followed up 420 first STEMI patients from the EARLY Assessment of MYOcardial Tissue Characteristics by CMR in STEMI (EARLY-MYO-CMR) registry (NCT03768453). These patients received timely primary percutaneous coronary intervention (PCI) within 12 h and CMR examination within 1 week (media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…22 Neisius U et al 23 used FT-CMR to detect myocardial deformations in 244 consecutive patients and were able to distinguish between hypertensive heart disease and hypertrophic cardiomyopathy. Lai W et al 24 studied early CMR myocardial tissue characteristics in 420 patients with first-time STEMI and in 40 patients without obvious heart disease (the control group). Their results showed that the strain values of left and right ventricles in patients with STEMI were significantly lower than those in controls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22 Neisius U et al 23 used FT-CMR to detect myocardial deformations in 244 consecutive patients and were able to distinguish between hypertensive heart disease and hypertrophic cardiomyopathy. Lai W et al 24 studied early CMR myocardial tissue characteristics in 420 patients with first-time STEMI and in 40 patients without obvious heart disease (the control group). Their results showed that the strain values of left and right ventricles in patients with STEMI were significantly lower than those in controls.…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that during the early stages of myocardial infarction, an FT-CMR film sequence examination without contrast agent, combined with myocardial strain measurements, can help clinicians to quickly identify chest pain causes, predict whether patients with AMI have STEMI, reveal the infarct scope and the arteries involved, provide imaging support to prevent adverse cardiovascular events, avoid reception delays, and reduce the incidence of adverse clinical prognoses. [24][25][26] Limitations: Our study was mainly a retrospective casecontrol study with a small sample size, without in-depth studies on the impact of FT-CMR on LGE negative sites or the number and location of culprit vessels in patients with STEMI. In addition, we did not assess the impact of baseline data such as age or gender, and we did not analyze the peak strain in each direction during systole.…”
Section: Discussionmentioning
confidence: 99%
“…Effective recanalization of the infarcted artery in patients treated with mechanical thrombectomy is high (approximately 90%), and 30-day mortality has decreased from more than 20% to less than 5% with widespread use of reperfusion therapy for STEMI [35]. Compared with men, women who receive less inappropriate treatment during AMI have worse outcomes than men with either thrombolytic therapy or PCI strategy, with higher morbidity and mortality when treated with thrombolytic drugs, in part due to confounding by risk factors such as age, diabetes, hypertension, and heart failure [36]. Data show that compared with elderly patients, young patients are more likely to have left anterior descending artery related myocardial infarction [37] [38].…”
Section: Epidemiologymentioning
confidence: 99%